The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.2166/wst.2003.0585
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification of high strength ammonia wastewater and nitrite accumulation characteristics

Abstract: Biological nitrogen removal via the nitrite pathway in wastewater treatment is very important in saving the cost of aeration and as an electron donor for denitrification. Wastewater nitrification and nitrite accumulation were carried out in a biofilm airlift reactor with autotrophic nitrifying biofilm. The biofilm reactor showed almost complete nitrification and most of the oxidized ammonium was present as nitrite at the ammonium load of 1.5 to 3.5 kg N/m3 x d. Nitrite accumulation was stably achieved by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…Ammonia oxidizers formed a dense layer of cell clusters in the upper part of the nitrifying biofilm from the trickling filter of an aquaculture water recirculation system, whereas the nitrite oxidizers showed lessdense aggregates in close vicinity to the Nitrosomonas clusters (Schramm et al 1996). This distribution pattern was supported by Kim et al 2003. It was reasoned out in the same publication that dissolved oxygen deficiency or limitation in the inner part of the nitrifying biofilm, where nitrite oxidizers exist, is responsible for the complete shut down of the nitrite oxidizers activity under the absence of FA inhibition.…”
Section: Fluorescence In Situ Hybridization Techniquementioning
confidence: 70%
See 1 more Smart Citation
“…Ammonia oxidizers formed a dense layer of cell clusters in the upper part of the nitrifying biofilm from the trickling filter of an aquaculture water recirculation system, whereas the nitrite oxidizers showed lessdense aggregates in close vicinity to the Nitrosomonas clusters (Schramm et al 1996). This distribution pattern was supported by Kim et al 2003. It was reasoned out in the same publication that dissolved oxygen deficiency or limitation in the inner part of the nitrifying biofilm, where nitrite oxidizers exist, is responsible for the complete shut down of the nitrite oxidizers activity under the absence of FA inhibition.…”
Section: Fluorescence In Situ Hybridization Techniquementioning
confidence: 70%
“…The most critical condition that is needed for the success of the SBNR process is to suppress nitrite oxidation without excessively retarding the ammonia oxidation rate. Generation and maintenance of a nitritation reactor requires that either the NOB are washed out from the biomass or their spatial distribution is such that they can no longer find suitable conditions under which to reestablish them (for example the inner part of the biofilm; Kim et al 2003). Unfortunately, ammonia-and nitrite-oxidizing bacteria can be found almost everywhere and therefore it might be difficult to find conditions favoring one over the other (Egli et al 2003).…”
Section: Shortcut Biological Nitrogen Removal (Sbnr)mentioning
confidence: 99%
“…The spatial distribution of AOB and nitrite oxidizing bacteria have been studied using fluorescent in situ hybridization (FISH) experiments. These studies revealed that AOB occupied the outside layers of the biofilm, whereas NOB were found in the deep layers of the biofilm (Kim et al, 2003). Thus, in a biofilm system NOB are more exposed to oxygen limiting conditions than AOB, and the diffusion resistance of oxygen into the biofilm offers selective growth of AOB ( Joo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Partial nitrification relies on the selection of AOB over nitrite-oxidizing bacteria (NOB), which allows the accumulation of nitrite. Sustained nitrite accumulation can be accomplished by controlling solids retention time, temperature, free ammonia and hydroxylamine concentrations, or dissolved oxygen (DO) conditions (2,12,15,19,23,42).…”
mentioning
confidence: 99%